Flow Characteristic Analysis of the Self-Priming Pump Based on the Population Balance Model - Chang, Hao; Hong, Shiming; Yu, Dehui; Peng, Guangjie; Du, Jialin; Yuan, Shouqi (Frontiers in Energy Research, 2022)
Self-priming pumps, as important two-phase fluid machinery, are widely used in disaster relief and emergency fields. The flow characteristics of the air–liquid two-phase fluid play an essential role in the self-priming pump performance. However, the traditional simulation employed the single-diameter bubbles for analysis, which cannot reflect the internal flow field characteristics. Therefore, in this article, the Population Balance Model (PBM) is employed, which divides the bubble into different diameter groups, and the collision and coalescence between the bubble are considered in the calculation to investigate the influence of different air voids and flow conditions on the performance self-priming centrifugal pumps. The result shows that the frequency of bubble coalescence at the shroud is higher, which is conducive to the formation of large-sized bubbles. Meanwhile, the increment of flow conditions has a significant effect on reducing the pressure pulsation of the gas–liquid two-phase flow, while the improvement of the air voids not only destroys the instability and asymmetry of the internal flow of the two-phase flow but also aggravates the amplitude of pressure pulsation, increasing the surface loading of the blade and radial force. Therefore, this article can provide a certain theoretical reference for the study of air–liquid two-phase flow characteristics of self-priming centrifugal pumps.